ANALYSIS OF THE DEVELOPMENT OF PHYSICS IN THE XXI CENTURY - Туксанова Зилола Изатуллоевна; Назаров Эркин Садикович; Мусоева Гулрух Сирожиддин кизи (Web of Journals Publishing, 2025)
In the 21st century, physics continues to occupy a key place in scientific progress and technological development of mankind. This article examines the main directions and achievements of physics over the past two decades, including nanophysics, quantum technologies, astrophysics, as well as the impact of the discovery of new particles and phenomena on our understanding of the universe.
Keywords: Quantum dot, atom, molecule, progress, matter, geology, mechanics, nucleus, photoelectric effect, thermonuclear fusion, nanosize, laser, superconductivity, multilayer elements.